2D Groundwater Depth for Analysis of The Zone Unconfined Aquifer - M Juandi; Muh Sarkowi (Universitas Lampung, 2016)
Abstract—Changes in land use have occurred quite significant in the city of Pekanbaru. The increasing of building spaces, the decreasing of plantations and forests are continues to grow with the increasing of population and industries. This means, it can cause impact on groundwater resources. This condition shall continue in effect, along with the population and industrial growth. This means, it can cause impact on groundwater resources of Pekanbaru City, thus the analysis of groundwater zone of Pekanbaru city is needed. The data used in this research is related with the biophysical and social economic. Data analysis method was using numeric simulation programming using finite difference method. The results showed that in 2016, its depth ranges between 16-46 m, this indicates that the unconfined aquifer was in trapped position but not included to the confined aquifer system. In 2017, it was predicted that the depth is about 6-38 m, and in 2018 the depth of unconfined aquifer will go deeper to 31,4-34 m. This is influenced by the changes of population and industrial and the automation of extraction of groundwater by those population and industrial is getting bigger. While in 2019 and 2020, the depth of the unconfined aquifer will be between 41,8-44,4 m and 44-46,8 m. It was predicted that the growth of population and industries will grow rapidly in the future. This rapid growth will cause the damage of the aquifer. Keywords—Zone, groundwater, numerical method.